ILC2s and Adipose Tissue Homeostasis: Progress to Date and the Road Ahead - Misawa, Takuma; Wagner, Marek; Koyasu, Shigeo (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) were initially identified as a new type of lymphocyte that produces vigorous amounts of type 2 cytokines in adipose tissue. Subsequent studies revealed that ILC2 is present not only in adipose tissue but also in various other tissues such as lung and skin. ILC2 is generally recognized as a tissue-resident immune cell that regulates tissue homeostasis. ILC2 expresses receptors for various humoral factors, making them a “chameleon-like cell” that can change its functions or distribution depending on the environment and circumstances. In this review, we will outline our recent understanding of ILC2 biology and discuss future directions for ILC2 research, particularly in adipose tissue and metabolic homeostasis.